Visualising and Simulating the Past Life of Weld Quay in the Early Twentieth Century: An Investigation through Narrative Analysis - Chan, Yi Chee; Idris, Muhammad Zaffwan; Lim, Chen Kim (Archives of Business Research, 2018)
From the late eighteenth century, British began their influence over the Malayan Peninsula. The three outposts of Penang, Singapore and Malacca then became the Straits Settlements in 1826. Weld Quay displayed an important role as one of the trading ports that represented hustle and bustle life of Penang during the early twentieth century. Many large and significant European companies, agencies and a few jetties were established and built along the Weld Quay for merchant business, mooring tongkangs or boats and uploading or downloading trading goods. However, those remarkable scenes are long gone, especially those intangible cultural heritages including the social and trading activities as well as intercultural discourse. One can safely presumed that these items are more unlikely to exist nowadays. Cultural heritage especially the intangible one is considered as fragile assets, thus it is imperative to preserve them. Unlike intangible, the tangible cultural heritage such as buildings, monuments and artifacts are considered easier to be preserved. Undoubtedly, the potential strategy to preserve the intangible cultural heritage in Weld Quay lies on the visualisation and simulation using the advanced digital technology. Since the intangible heritage is no longer existing, a method called narrative analysis is preferred to systematically gather as much as possible data in order to accurately visualise and simulate the past life. The digital constructions of the site, both tangible and intangible are significant for future generation in order to cherish the remarkable moment and past achievement enfolded in Weld Quay.